2015
DOI: 10.1038/ejhg.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Screening of dementia genes by whole-exome sequencing in early-onset Alzheimer disease: input and lessons

Abstract: Causative variants in APP, PSEN1 or PSEN2 account for a majority of cases of autosomal dominant early-onset Alzheimer disease (ADEOAD, onset before 65 years). Variant detection rates in other EOAD patients, that is, with family history of lateonset AD (LOAD) (and no incidence of EOAD) and sporadic cases might be much lower. We analyzed the genomes from 264 patients using whole-exome sequencing (WES) with high depth of coverage: 90 EOAD patients with family history of LOAD and no incidence of EOAD in the family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 46 publications
(45 reference statements)
1
71
0
Order By: Relevance
“…Nicolas et al (Nicolas et al ., 2015) screened 264 EOAD samples and found three samples (1%) heterozygous for one of three PSEN1 variants that are possibly or probably pathogenic; they also found one sample (0.4%) heterozygous for a causative PSEN2 mutation. None of the patients in this study harboured APP mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Nicolas et al (Nicolas et al ., 2015) screened 264 EOAD samples and found three samples (1%) heterozygous for one of three PSEN1 variants that are possibly or probably pathogenic; they also found one sample (0.4%) heterozygous for a causative PSEN2 mutation. None of the patients in this study harboured APP mutations.…”
Section: Resultsmentioning
confidence: 99%
“…We studied 111 EOAD patients without mutations in the known AD genes and 292 healthy individuals from the Knight ADRC at Washington University by Sanger sequencing and we assessed exome sequencing data available on 484 French EOAD patients and 498 French controls without mutation in the known AD genes. Interestingly, we identified and confirmed by Sanger sequencing two rare coding variants in three unrelated French patients (Nicolas, et al, 2015), whereas no rare coding variants were detected in controls (n=595 EOAD patients and n=790 healthy subjects, Table 3, Supplementary Table 3). When combining these results, we observed a significant association between rare coding variants and EOAD: 6 rare coding TYROBP variants were identified in 9 unrelated patients out of 1110 white non-Hispanic EOAD patients as compared to an absence of such variants in 1826 healthy subjects (p-value=0.0001; CMC test).…”
Section: Resultsmentioning
confidence: 73%
“…Moreover, compared with the earlier analyses between 1989 and 2010 where there were notable rises in males in six countries and in four countries for females, by 2014 there had been rises of equivalent to >10% in twelve countries for men and in eleven countries for females. A Gompertzian perspective also ignores rises in early onset dementia (EOD) reported in many countries 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 19, 20, 22, 25. For example, one found 29% of their cohort were aged under 65 years, which 30 years before would have been considered extraordinary 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 19, 20, 22, 25.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to discount studies that identified genetic and familial patterns20, 21, 22 but others recognize lifestyle and possible interactive environmental contributions 2, 4, 6, 7, 8, 25. Including such factors as occupation, heavy metals, petro‐chemicals, organophosphate/pesticides26, 27, 28, 29, 30 and possible influence of electromagnetic field (EMF)18, 25, 31 and military service 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation